(untitled) (Journal of Misan Researches, 2023)
This study examines the topic (Political Developments in the Maldives and the British Position on them 1954 – 1965) as that stage witnessed influential political transformations in the country. He enacted a new constitution for the country, developed a plan to modernize the country, and signed in 1956 with the British a preliminary agreement on renting the Jan military base, which caused an internal crisis in the country, after which the three southern islands (Fawamullah, Thinadu and Addu Atoll) separated from the central government, and formed a republic After that, the Jan Agreement was amended in February 1960 during the era of Maldivian Prime Minister Ibrahim Nasir, who led the country’s diplomacy, and could resolve most of the complex matters in the country after negotiating with the British on two important issues the first, the restoration of The separatist islands to the authority of the central government, and the second, to negotiate for the complete independence of the country, and after negotiations with the British returning the three islands to the authority of the central government in 1963, and could achieve The country’s transition in July 1965, and the Maldives freed from British domination, which lasted more than a century and a half.